2009
DOI: 10.1121/1.3021304
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of interrupted sentences at subsegmental levels in young normal-hearing and elderly hearing-impaired listeners

Abstract: Although listeners can partially understand sentences interrupted by silence or noise, and their performance depends on the characteristics of the glimpses, few studies have examined effects of the types of segmental and subsegmental information on sentence intelligibility. Given the finding of twice better intelligibility from vowel-only glimpses than from consonants ͓Kewley-Port et al. ͑2007͒. "Contribution of consonant versus vowel information to sentence intelligibility for young normal-hearing and elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…No such duration constraint on the M-level segmentation was imposed in this study. We believe this might account for the discrepancy on the role of C-V boundaries for intelligibility prediction between the present study and the study by Lee and Kewley-Port (2009). Further studies are warranted to assess the effect of segment duration (containing C-V boundaries) to intelligibility prediction.…”
Section: B Contributions Of Vowel-consonant Boundaries To Sentence Icontrasting
confidence: 50%
See 2 more Smart Citations
“…No such duration constraint on the M-level segmentation was imposed in this study. We believe this might account for the discrepancy on the role of C-V boundaries for intelligibility prediction between the present study and the study by Lee and Kewley-Port (2009). Further studies are warranted to assess the effect of segment duration (containing C-V boundaries) to intelligibility prediction.…”
Section: B Contributions Of Vowel-consonant Boundaries To Sentence Icontrasting
confidence: 50%
“…This same vocalic segment, however, was classified as an H-level segment and not as an M-level segment. Lee and Kewley-Port (2009) recently examined the intelligibility of interrupted sentences (using the noise-replacement paradigm) preserving four different types of sub-segmental cues, namely steady-state cues at centers or transitions of vowel-consonant margins, and vowel onset or offset transitions. They found that intelligibility scores were not significantly different among the various types of sub-segmental information used.…”
Section: B Contributions Of Vowel-consonant Boundaries To Sentence Imentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation depends, however, on vowel and vowel-like sounds being amply kinematic to convey substantial change. In fact, contrary to customary consideration of vowels as being "quasistationary" (13), frequencies of vowel formants in North American English change substantially over time with the exception of high vowels /i/ and /u/ (31, 32). In studies concerning limited classes of speech sounds, some investigators have been drawn to the significance of spectral change for perception [e.g., formant transitions for Cs (33), Vs (31), or CVCs (9)].…”
mentioning
confidence: 99%
“…On average, "vowel" segments of sentence waveforms are roughly one-third longer than "consonant" segments in American English. Very recently, Kewley-Port and colleagues (13) provided evidence that there may be no intelligibility differences between replacing consonants (Cs), vowels (Vs), or transitions (CVs, VCs) after accounting for duration.…”
mentioning
confidence: 99%